A Systematic Review on Intensity Modulated Radiation Therapy for Mediastinal Hodgkin's Lymphoma. (November 2021) - Buglione, Michela; Guerini, Andrea Emanuele; Filippi, Andrea Riccardo; Spiazzi, Luigi; Pasinetti, Nadia; Magli, Alessandro; Toraci, Cristian; Borghetti, Paolo; Triggiani, Luca; Alghisi, Alessandro; Costantino, Gianluca; Bertagna, Francesco; et al.
Graphical abstract: Highlights: Late RT toxic effects play a central role in long-term survivorship of HL patients. IMRT could significantly reduce doses to the heart and cardiac sub-structures. Increased risk of SMNs due to low dose spread using IMRT is still unclear. Dedicated techniques might decrease the irradiation of the breasts and lungs. RT planning should always be tailored on each patient comparing multiple rival plans. Abstract: Background: Secondary malignant neoplasms (SMNs) and cardiovascular diseases induced by chemotherapy and radiotherapy represent the main cause of excess mortality for early-stage Hodgkin lymphoma patients, especially when the mediastinum is involved. Conformal radiotherapy techniques such as Intensity-Modulated Radiation Therapy (IMRT) could allow a reduction of the dose to the organs-at-risk (OARs) and therefore limit long-term toxicity. Methods: We performed a systematic review of the current literature regarding comparisons between IMRT and conventional photon beam radiotherapy, or between different IMRT techniques, for the treatment of mediastinal lymphoma. Results and conclusions: IMRT allows a substantial reduction of the volumes of OARs exposed to high doses, reducing the risk of long-term toxicity. This benefit is conterbalanced by the increase of volumes receiving low doses, that could potentially increase the risk of SMNs. Treatment planning should be personalized on patient and disease characteristics. Dedicated techniques such as "butterfly" VMAT often provide the best trade-off.